Comorbid Autoimmune Diseases in Patients With Myasthenia Gravis: A Retrospective Cross-Sectional Study of a Chinese Cohort - Shi, Jianquan; Huan, Xiao; Zhou, Lei; Xi, Jianying; Song, Jie; Wang, Ying; Luo, Sushan; Zhao, Chongbo (Frontiers in Neurology, 2021)
Introduction: The phenomenon of coexisting autoimmune diseases (ADs) in patients with myasthenia gravis (MG) has attracted considerable attention. However, few studies have investigated the burden and potential clinical associations of ADs in Chinese MG cohorts. Methods: In this retrospective cross-sectional study, we reviewed the records of 1132 patients with MG who were admitted to Huashan Hospital Fudan University from August 2013 to August 2020. Patients were excluded if they had incomplete medical records (n = 336). Results: Comorbid ADs were found in 92 of 796 Chinese patients with MG (11.6%), among which, hyperthyroidism (6.7%), hypothyrosis (2.6%), and vitiligo (0.8%) were predominant. Patients with MG with ADs were predominantly female, younger at the onset of MG symptoms, and had a lower frequency of thymoma. Compared to the general population, we found a significantly higher percentage of hyperthyroidism (8.5-fold increase, p < 0.001), hypothyrosis (2.6-fold increase, p < 0.001), vitiligo (1.3-fold increase, p < 0.001), rheumatoid arthritis (1.4-fold increase, p < 0.001), immune thrombocytopenic purpura (193.1-fold increase, p < 0.001), autoimmune hemolytic anemia (7.4-fold increase, p < 0.001), autoimmune hepatitis (5.1-fold increase, p < 0.001), and polymyositis (11.5-fold increase, p < 0.001) in patients with MG with ADs. Patients with MG with ADs presented a lower proportion of previous history of MC (0% vs 5.6%, p < 0.05) than those without ADs. The proportion of MGFA Class I at onset in patients with MG with ADs was significantly higher than that in patients with MG without ADs (77.0% vs 52.7%, p < 0.05). The proportion of MuSK-positive in patients with MG with ADs was significantly lower than that in patients with MG without ADs (0% vs 4.8%, p < 0.05). Conclusion: In conclusion, we observed a higher frequency of concurrent ADs in a Chinese MG cohort. Furthermore, MG combined with ADs tended to have mild clinical presentation.